Consumers’ Behavioural Intention to Adopt Mobile Banking in Rural Sub-Saharan Africa Using an Extension of Technology Acceptance Model: Lessons from Zimbabwe - Muzurura, Joe; Chigora, Farai (International Journal of Business, Economics and Management, 2019)
The zeitgeist of mobile banking epoch in Sub-Saharan Africa has marked a fundamental transition from the use of physical currency, debit/credit cards and cheques towards a mobile banking e-commerce. In these countries mobile banking provides consumers with added-on advantages such as user-friendliness, cost effective, fast transaction speeds and increased customer satisfaction. Despite the popularity of mobile banking, consumers in most rural areas have largely remained excluded from such beneficial financial innovation. In addition, the extent to which mobile banking services are being adopted by rural consumers has not increased as expected, yet, economic growth and development of Sub-Saharan Africa could fundamentally be contingent on how these potential consumers adopt and use mobile banking innovations. The main objective of the study was to examine the adoption of mobile banking in Sub-Saharan African rural areas drawing lessons from Zimbabwe. Quantitative data was collected using a questionnaire from a random sample of 100 respondents. The findings show that the likelihood of adopting mobile banking in rural Sub-Saharan Africa regions are influenced by perceived usefulness, compatibility perceived ease of use and demographic factors. The likelihood of deferring the adoption of mobile banking are due to complexity, relative advantages, perceived usefulness, social influence and perceived risk. The study recommends policies that reduce perceived risk and complexity, increase trust, confidentiality and awareness knowledge among rural user.